Uplink and Downlink of LTE-Release 10 in Cellular Communications - Aws Yonis; M.F.L. Abdullah (International Journal of Informatics and Communication Technology (IJ-ICT), 2012)
In LTE-Advanced, orthogonal frequency division multiple access (OFDMA) has been selected as the multiple access scheme for downlink and single-carrier frequency division multiple access (SC-FDMA) for uplink. OFDM is an attractive modulation technique in a cellular environment to combat frequency selective fading channels with a relatively low- complexity receiver. However, OFDM requires an expensive and inherently inefficient power amplifier in the transmitter due to the high peak-to-average power ratio (PAPR) of the multicarrier signal. This paper, presents the main components of LTE-Advanced including the all the details of Uplink (SC-FDMA) and Downlink (OFDMA). Also this paper clarifies the main reasons of using SC-FDMA in uplink and using OFDMA in downlink only, in order to obtain flexible mobile communication technology.DOI: http://dx.doi.org/10.11591/ij-ict.v1i1.557